Recruitment and virtual selection by skills - Valeriano Ortiz, Luis Fernando (2021)
Globalized and national companies that develop in a world of turbulence and uncertainty as a result of the COVID-19 pandemic, which has generated political instability, economic crisis, loss of jobs, among other restrictive aspects, require a sustainable, inclusive and resilient by building digital technology platforms to optimize business management. In that order of ideas, companies need to recruit, select and hire personnel for their different work positions, endowed with knowledge of science, technology and humanities that knowledge societies demand and with soft skills such as emotional intelligence required to ensure efficient, effective and effective development in the fulfillment of the assigned functions or tasks. The pandemic, which is lethal in the field of physical and mental health of people, has allowed us to use digital tools such as work and remote or virtual education with satisfactory results using social networks to guarantee the development of the economies of the countries. Companies apply the recruitment, selection and hiring of personnel by competencies in a virtual way through the development of their technical processes, minimizing costs and maximizing results.